Positive youth development through taekwondo: a journey to the black belt - Lee, Yongsun; Lim, Seami (Frontiers in Psychology, 2025)
IntroductionThis study explored the role of Taekwondo (TKD) in fostering Positive Youth Developmental (PYD) outcomes among young practitioners. Drawing on the Sport-Based Youth Development (SBYD) framework, it investigated how the black belt journey contributes to physical, social, and emotional growth.MethodsAn embedded case study design was used, focusing on four TKD academies in the Southeastern United States. Data sources included student handbooks, instructor manuals, black belt essays, and recommendation letters. Thematic analysis was employed to analyze the qualitative data.ResultsFindings revealed that (1) the black belt journey offered a holistic experience integrating physical skill development with life skill acquisition; (2) the belt ranking system facilitated structured goal setting and achievement; and (3) core life skills such as perseverance, integrity, and leadership were intentionally taught within the TKD curriculum across all academies.DiscussionThe study suggests that TKD can serve as an effective context for promoting PYD when it includes opportunities for setting goals, receiving behavioral guidance, and learning transferable life skills. The integration of goal-oriented progression and character education appears to be key in supporting youth development through martial arts.